Advancements related to probiotics for preventing and treating recurrent respiratory tract infections in children - Yali Zhang; Yali Zhang; Yingying Xu; Yingying Xu; Ling Hu; Ling Hu; Xiaomei Wang (Frontiers in Pediatrics)
Recurrent respiratory tract infections (RRTIs) are a common condition in pediatrics and significantly impact children's quality of life; however, their pathogenesis and contributing factors are not yet fully elucidated. Probiotics have recently emerged as promising agents for modulating intestinal microecology and have gained considerable attention in clinical research on preventing and treating RRTIs in children. This article provides an initial overview of the concept, classification, and mechanisms underlying probiotics. It emphasizes their beneficial effects on respiratory health by modulating intestinal microbial equilibrium, augmenting immune system functionality, and attenuating inflammatory responses. Subsequently, we examine existing research regarding the use of probiotics in pediatric RRTIs. Numerous clinical trials have unequivocally demonstrated that supplementing with probiotics can significantly reduce both the frequency and severity of RRTIs in children while also simultaneously decreasing antibiotic usage. However, there are ongoing controversies and challenges in current research concerning the influence of probiotic type, dosage, duration of use, and other factors on efficacy. Furthermore, variations have been observed across different studies. Additionally, it is crucial to further evaluate the safety and potential long-term side effects associated with probiotic use in children with RRTIs. In conclusion, we propose future research directions including conducting more high-quality randomized controlled trials to optimize application strategies for probiotics alongside other treatments while considering variations based on age and health conditions among pediatric populations. Finally, in summary although probiotics exhibit promising benefits in preventing and treating RRTIs in children; additional studies are necessary to refine their application strategies ensuring both safety and effectiveness.